SASIEv.1: a framework for seasonal and multi-centennial Arctic sea ice emulation - S. M. Chilcott; S. M. Chilcott; M. Meinshausen; D. Notz (Geoscientific Model Development)
The high computational expense of complex climate models and their tendency to underestimate observational records of Arctic sea ice sensitivity to anthropogenic forcers challenge our ability to assess the magnitude of forcing that will cause Arctic sea ice loss to cross critical thresholds. To address these limitations, we develop a parameterisation framework for Arctic sea ice emulation, SASIEv.1, that is calibrated to the response of sea ice area to global warming in physically-based CMIP6 models and constrained to observations. Our constrained framework reduces the remaining budget of CO2 that can be emitted while preventing seasonally ice-free conditions from 821 Gt CO2 by CMIP6 multi-model ensemble estimates to 380 Gt CO2. This suggests that limiting global warming to 1.5 °C is sufficient to prevent a seasonally ice-free Arctic Ocean, whereas 2 °C proves insufficient. Our results also provide insight into the future of winter sea ice over a greater ensemble range than previously possible, pinpointing the emission threshold at which the ice pack detaches from land, after which the ice pack rapidly disappears to year-round ice free conditions.